Sensorial, physical and chemical evaluation of bio-fortified Ipomoea batatas - Mara N.G. Santos; Joice V.C. Orsine; Alexandre I. de A. Pereira; Roberto Cañete; María R.C.G. Novaes (GarVal Editorial Ltda., 2014)
Context: Bio-fortified sweet potato, Ipomoea batatas (L.) Lamarck beta-carotene rich, has been included in the most vulnerable population's diet with the purpose of reducing health disturbances associated with hipovitaminosis. Aims:To evaluate a physical and chemical analysis of total carotenes and beta-carotene and to determine the antioxidant potential as well as to carry out a sensorial analysis of the bio-fortified Ipomoea batatas (L.) Lamarck (BDB) in nature and processed. Methods: BDB was processed as sweet (in natura, paste and syrup) and physicochemical characteristics were compared, total carotenoids, beta-carotene, antioxidant activity (DPPH) and microbiological and sensory analyses were performed. Results:The analysis of total carotenoids, beta-carotene and anti-oxidant potential showed the following results: BDB in nature - 11.81 mg/100 g/440.5 mg/100 g/26.30%; sweet paste - 0.61 mg/100 g/53.5 mg/100 g/53.40% and savored syrup - 0.85 mg/100 g/46.0 mg/100 g/14.30%. The methods of conservation avoided the coliforms growth at 35 and 45°C, Staphylococcus coagulasa positivo, Bacillus cereus and Salmonella in all elaborated candies. The sensorial analysis didn't detect significant differences among the syrup or paste. Conclusions: The conservation methods have an important function keeping the physical, chemical characteristics and sensorial of BDB, although they can influence in their chemical and nutritional composition, mainly in relation to the quantity of total carotenoids and beta-carotene.